Financial technologies development prospects in the countries of Eastern Europe and Ukraine - Abramova, A; Beschastnyy, V.; Zhavoronok, А.; Fedyshyn, M.; Lavrov, R.; Dluhopolskyi, O.; Kozlovskyi, S. (International Journal of Management, 2021)
Analysis of the implementation of financial technologies (FinTech) has shown that their use causes the rapid transformation of financial services into new forms, expands the possibilities of their use. In these conditions, the economic feasibility of studying the foreign experience of FinTech development increases. The subject of the research is instrumental and mathematical aspects of modeling the influence of factors on the functioning of FinTech in Hungary, Poland, Slovakia, Romania and Ukraine. The aim of the work is to study components of the infrastructure and factors influencing the FinTech functioning in the Eastern Europe countries and Ukraine based on the construction of a multi-factor econometric model as a basis for making effective management decisions to ensure sustainable development of the financial services market in Ukraine. It examined through hypotheses different scenarios of the impact of factors such as: GDP, population, consumer spending and Internet access on the functioning of FinTech. It is determined that the priority areas and tools for the development of FinTech in Ukraine are: modernization of FinTech business models in the direction of the technology development and customer needs, partnerships and cooperation with banking institutions; use of services of your own IT companies or software of well-known international suppliers such as SAP; overcoming the problem of the financial services market development in Ukraine due to low mentality and lack of financial literacy on the basis of building the institute of trust; formation of the favorable investment climate for the financial assets inflow for the FinTech development.
Keywords: bank, insurance company, investment fund, FinTech company, financial services market.